2017
DOI: 10.1080/09537287.2017.1374485
|View full text |Cite
|
Sign up to set email alerts
|

Strategic approaches to sustainability in fashion supply chain management

Abstract: Today, the sustainability challenge has become a relevant issue in the fashion industry. However, given that the request for sustainability is relatively new in this industry, empirical research that could guide companies towards supply chain sustainability is lacking. This study aims to deepen the understanding of the main strategic approaches to sustainability used in fashion supply chain management (SCM). Ten case studies were examined in terms of the practices that characterise these approaches. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 102 publications
0
60
0
1
Order By: Relevance
“…To study these challenges, most studies related to the CSR of fashion companies fall into three groups: studies focusing on pursuing sustainable growth through protection of workers' and suppliers' rights and the environment (e.g. Lion et al, 2016;Lueg et al, 2015;Macchion et al, 2015Macchion et al, , 2017Macchion et al, , 2018Perry and Towers, 2009); studies related to CSR communication since fashion companies use CSR as a tool to improve their image (e.g. Da Giau et al, 2016;Guercini, 2001); and empirical studies focusing on how consumers' cognitive responses to fashion companies' CSR affect consumer behavior (e.g.…”
Section: Csr In the Fashion Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…To study these challenges, most studies related to the CSR of fashion companies fall into three groups: studies focusing on pursuing sustainable growth through protection of workers' and suppliers' rights and the environment (e.g. Lion et al, 2016;Lueg et al, 2015;Macchion et al, 2015Macchion et al, , 2017Macchion et al, , 2018Perry and Towers, 2009); studies related to CSR communication since fashion companies use CSR as a tool to improve their image (e.g. Da Giau et al, 2016;Guercini, 2001); and empirical studies focusing on how consumers' cognitive responses to fashion companies' CSR affect consumer behavior (e.g.…”
Section: Csr In the Fashion Industrymentioning
confidence: 99%
“…Contingency models show that CSR triggers the corporate image building process (Arendt and Brettel, 2010). Brown and Dacin (1997), Macchion et al (2018), andDa Giau et al (2016) ascertained that CRS positively affects consumers' evaluations of companies and products, which imply that CSR should facilitate a favorable corporate image (Vanhamme et al, 2012). They also stressed that CSR is one of the factors that influences the public to determine the image of companies.…”
Section: Corporate Imagementioning
confidence: 99%
“…Research models show that corporate social responsibility activates the process of creating a corporate image (Arendt and Brettel, 2010). Da Giau et al (2016) and Macchion et al (2018), found that corporate social responsibility positively affects consumer ratings of companies and products or services. At the same time, Fatma et al (2015), demonstrated that corporate social responsibility initiatives are successfully strengthening the positive corporate image in the minds of customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simultaneously, the number of research articles concerned with SCM and the various dimensions of sustainability (environmental or social sustainability) has increased exponentially (Hassini et al, 2012;Croom et al, 2018;Macchion et al, 2018;Saberi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%